2011
DOI: 10.1016/j.atherosclerosis.2010.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Markers of atherosclerosis and inflammation and mortality in patients with HIV infection

Abstract: Objective-HIV-infected patients are at increased risk for cardiovascular disease, which may be mediated in part by inflammation. Surrogate marker studies suggest an increased prevalence of vascular abnormalities in HIV infection. We examined the association of all-cause mortality in HIV-infected patients with carotid artery intima-media thickness (cIMT) and high-sensitivity Creactive protein (hsCRP).Design and Methods-Baseline risk factors, cIMT and hsCRP were prospectively measured in 327 HIV-infected partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 39 publications
1
35
2
1
Order By: Relevance
“…Charakida et al showed that cIMT and FMD were elevated in HIV-infected children, particularly those taking a protease inhibitor (PI)-containing regimen (Charakida et al, 2005). Increased cIMT has been widely reported in HIV-infected populations (Chironi et al, 2003;Hsue et al, 2009a;Hsue et al, 2004;Lorenz et al, 2008;Mercie et al, 2005;Oliviero et al, 2009;van Vonderen et al, 2009), is strongly associated with all-cause mortality in HIV patients (Mangili et al, 2011), and appears to be associated with both HIV infection and HAART regimen (Chironi et al, 2003;Lorenz et al, 2008). Protease inhibitors have been implicated as a mediator of increased cIMT (Maggi et al, 2004).…”
Section: Haart-naïve (N¼20)mentioning
confidence: 96%
“…Charakida et al showed that cIMT and FMD were elevated in HIV-infected children, particularly those taking a protease inhibitor (PI)-containing regimen (Charakida et al, 2005). Increased cIMT has been widely reported in HIV-infected populations (Chironi et al, 2003;Hsue et al, 2009a;Hsue et al, 2004;Lorenz et al, 2008;Mercie et al, 2005;Oliviero et al, 2009;van Vonderen et al, 2009), is strongly associated with all-cause mortality in HIV patients (Mangili et al, 2011), and appears to be associated with both HIV infection and HAART regimen (Chironi et al, 2003;Lorenz et al, 2008). Protease inhibitors have been implicated as a mediator of increased cIMT (Maggi et al, 2004).…”
Section: Haart-naïve (N¼20)mentioning
confidence: 96%
“…The reasons for this phenomenon are likely complex, although recent studies suggested that chronic inflammation and immune activation/senescence may contribute to the initiation and progression of atherosclerosis in HIV infection (37,(140)(141)(142). LPS represents an important source of inflammatory stimuli (143) and has been investigated in the setting of atherosclerosis (144).…”
Section: Microbial Translocation In Cardiovascular Diseasementioning
confidence: 99%
“…Other markers of inflammation and kidney reserve have already been shown to correlate with future cardiovascular risk including hsCRP, D-dimer, and cystatin C levels [4,25,[62][63][64]. Interestingly, inflammatory markers themselves (such as hsCRP) can down-regulate adiponectin production, potentially explaining some of the predictive capabilities of these markers [65].…”
Section: Discussionmentioning
confidence: 99%
“…As HIV patients are living longer, they are increasingly developing cardiovascular and metabolic diseases, similar to the aging general population [1][2][3][4]. Additionally, some studies suggest that HIV patients are experiencing accelerated vascular aging [5,6], although further data are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation